2021
DOI: 10.1186/s41100-021-00322-2
|View full text |Cite
|
Sign up to set email alerts
|

Prescription characteristics of phosphate binders in a high pill burden for hemodialysis patients

Abstract: Background Dialysis patients have to take many oral drugs, causing a high pill burden. Phosphate binders (PBs) account for a large proportion of daily pill burden; however, the relationship between patient background and prescription status of PBs is not clear. Methods We clarified the characteristics of PBs in the total daily pill burden by analyzing the drugs prescribed for 533 chronic hemodialysis patients in our facility. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…This study is a post‐hoc analysis of a previously reported single‐center cross‐sectional study [10]. Of the 546 chronic hemodialysis patients at our dialysis center in the Heisei Hidaka clinic (Gunma, Japan), we excluded 13 patients who were not on stable hemodialysis during the study period (February 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is a post‐hoc analysis of a previously reported single‐center cross‐sectional study [10]. Of the 546 chronic hemodialysis patients at our dialysis center in the Heisei Hidaka clinic (Gunma, Japan), we excluded 13 patients who were not on stable hemodialysis during the study period (February 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The patient background, dialysis condition, serum chemistries, and comorbidities in 533 patients were described in detail in a previous report [10]. The median value of the total daily pill burden was 14.1 (10.0–18.7) pills/day/patient.…”
Section: Methodsmentioning
confidence: 99%
“…They are prescribed on average 9-12 types of medications and have a daily pill burden of 15-19 pills. [1][2][3] A recent study found that a larger number of medications is associated with a lower health-related quality of life (HRQoL) and a higher number of symptoms in dialysis patients. 3 The group of medications contributing most to dialysis patients' pill burden are phosphate binders which comprise 30%-50% of their pill burden.…”
Section: Introductionmentioning
confidence: 99%
“…3 The group of medications contributing most to dialysis patients' pill burden are phosphate binders which comprise 30%-50% of their pill burden. 1,2 These drugs are typically prescribed to manage hyperphosphatemia, one of the typical sequelae of chronic kidney disease and an important risk factor for cardiovascular disease and mortality. 4,5 Besides their high pill burden, phosphate binders, complicate medication regimens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation